Penerapan Kebijakan Kepala Sekolah Terhadap Pengembangan Profesi Guru - Qurban Hajar; Hen Ardiansyah; Siama (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This study aims to describe school policies for increasing teacher professionalism at SMP Negeri 1 Hu'u. This research also uses a qualitative descriptive approach with data collection methods in the form of observations, interviews, and document studies which are used as sources of primary data and secondary data. Primary data were obtained from observations and interviews with school principals and teachers. Secondary data is in the form of supporting data documents to strengthen the Implementation of School Policies in Increasing Teacher Professionalism at SMP Negeri 1 Hu'u, Dompu Regency. The results of the study show that: 1) the implementation of MGMP, PKB, Education, and Training activities, and curriculum development from the three schools are still lacking because not all teachers are sent to these activities. As well as the lack of readiness for teacher professional competence in the self-development sector and the use of technology, information, and communication. 2) The obstacles faced in the implementation of increasing teacher professionalism are ongoing professional development, namely the teacher's lack of understanding of teaching materials, and the lack of opportunities to attend training as support to becoming a professional teacher. 3) Efforts to address the obstacles encountered in the implementation of increasing teacher professionalism have been carried out related to the implementation of PKB, MGMP, curriculum development, and training at the school, regional and provincial levels but these achievements have not been fully maximized. The education office and schools need to continue to strive to improve teacher professionalism. This analysis has an impact on the creation of better education, improving the performance and quality of teachers to become professional teachers, and the realization of public understanding of the importance of education